An intervention development study of an mHealth app to manage women’s health and safety while on probation - Crawford, Allison D.; Salisbury, Emily J.; McGrath, Jacqueline M. (Health & justice, 2024)
Purpose Preliminary studies have suggested that women are responsive to using technology to manage their health, due to its discreet, convenient, and cost-effective nature. Yet, there are limited mobile health (mHealth) apps specific to women’s needs, particularly those on probation. The purpose of this study was to explore features of 2 existing mHealth applications related to sexual health and safety, specific to interpersonal and sexual violence, to answer research questions related to the usability, barriers, and facilitators of mHealth app use for women on probation. Subjects We purposefully sampled from a local adult probation site and utilized snow-ball sampling to recruit 11 women who were on probation and owned iPhones. Methods We conducted an exploratory intervention development study using a qualitative design. Social Cognitive Theory was used for data synthesize and organization. Findings Three themes emerged: (1) It made me take time for myself ; (2) It helped me to be more respectful of my body ; (3) The connectivity….that was helpful. Major implications Participants expressed mHealth apps to be usable, feasible, accessible and promoted self-efficacy by allowing them track symptoms and patterns of behavior specific to health and safety in a discreet, convenient, and effective manner. This research suggests that a culturally tailored mHealth app may be an appropriate intervention to provide timely gender-responsive feedback, resources, and health care to women on probation.